A conferência mundial de Durban sob a ótica da decolonialidade: o combate ao racismo em relação ao Sul global - Santos, Éwerton Clécio Viturino dos (2022)
The Third World Conference Against Racism, Racial Discrimination, Xenophobia and Related Intolerance, better known as The Durban World Conference, held in 2001 in Durban, South Africa, represented a milestone for world society in regarding the fight against racism in its various facets. In view of this, the present research aims to analyze the Durban World Conference in the light of decolonial theory, highlighting the relationship between racism and coloniality and its confrontation from the Global South. By taking decolonial thought as a current that investigates coloniality and the construction of measures that identify and seek to overcome its logic, it is understood that the factor of race, as a social and historical element, was fundamental in the expansion of the Western colonial project. and that racism is the result of its legacy, experienced mainly by the actors that make up the Global South, placed in the condition of subalternity. Thus, their confrontation cannot be detached from decolonial projects. In this way, it focuses on answering on which aspects the Durban World Conference contributed as a channel for the confrontation of racism and coloniality by the Global South. For this, it is configured in three specific objectives, which are (1) review the literature on Decolonialism and establish its relations with racism and the Global South; (2) describe the processes of articulation and development of the World Conference in Durban, as well as its Declaration and Plan of Action as a resultant instrument of combat; (3) analyze the articulations of social movements in the Global South, their histories and the construction of their agendas to face the negotiation processes of the Conference, and view such processes from a decolonial perspective. The methodology is bibliographic and documentary, historical-descriptive, case study and qualitative analysis. The argument is divided into three chapters. The first presents the discussions on what constitutes racism and the Global South, and contemplates these two concepts from the decolonial lens, while delving into this theoretical line. The second seeks to highlight the UN precedents against racism and the directions that gave rise to the said conference, at the same time as it deals with its developments and its final document. The third, in turn, intends to identify the main transnational articulations of social movements from the Global South and the construction of their agendas for the Conference and analyze them from a decolonial lens. Thus, the research seeks to establish the relationship of these representations with the Conference, in order to define considerations about their contributions to the confrontation of racism and coloniality in relation to the Global South.